Diversity of soil green algae in an oil palm plantation at Sungai Asap, Sarawak, Malaysia - Lim, Chin Tsong (2016)
Palm oil industry is the main contributor toward current Malaysia’s economy. Sarawak, being the largest state in Malaysia, contribute about 26% of total oil palm planted in Malaysia. Sustainable agriculture is closely related to the efficient use of natural resources, which is heavily dependent on soil microorganism activities. Hence, soil microorganisms often act as early indicator of soil quality as they respond rapidly to changes related to soil management. Soil green algae are mostly photosynthetically active microorganisms having changeable community structure, regardless to the soil type and agricultural practices. Hence, in this study, the diversity of soil green algae was investigated in an oil palm plantation and compared with the nearby secondary forest. Total soil microorganism DNA was extracted and soil green algae 18S rDNA was amplified using ChloroF and ChloroR primers set. Denaturing gradient gel electrophoresis (DGGE) was used to study the diversity of soil green algae communities of the oil palm plantation and the nearby secondary forest at Sungai Asap, Sarawak. Shannon-weaver index revealed that the diversity in oil palm plantation (OP) and disturbed secondary forest (S2) were higher than undisturbed secondary forest. The diversity index (H’) was increase over time for OP (3.1 to 3.3) and S2 (1.4 to 1.9), except undisturbed forest (S1: 1.8 to 1.6). Furthermore, species richness (1-D) was increased over time in S2 (2.3 to 3.0) and OP (3.1 to 3.3). Algae richness in S1 was nearly constant over time, which might be due to the soil in this area being undisturbed. In contrast, both OP and S2 were disturbed by planting and human activity, respectively. Cluster analysis based on operational taxonomic unit (OTUs) divided the banding patterns mainly into three main clusters, which were the three sampling sites. DGGE profile of OP was preferentially related to S2 during wet season (December) while it was closer to S1 during dry season (June). However, clusters similarity decreased over time, suggesting green algae community of the three sampling sites became more distinct over the sampling period. Diversity indices were significantly correlated to soil exch. K, exch. Ca, exch. Mg and total N at OP which might due to the fertilization activity. A total of 126 prominent DGGE bands were excised and sequenced for phylogenetic analysis. The diversity of soil green algae in the OP was higher than the S2, followed by S1. Chlamydomonadales, Sphaeropleales, Chaetophorales, Trebouxiales and Chlorococcales were among the dominant order of green algae found in this sampling area. Therefore, this study delivered an overview of the composition, diversity, and community structure of soil green algae in oil palm plantation and the nearby secondary forest at Sungai Asap, Sarawak. Generally, the soil chemical properties of secondary forest, especially undisturbed soil, was better than OP. However, it can be concluded that OP soil is still healthy as the soil green diversity and richness was increased over time. The knowledge of soil green algae diversity was obtained and hence lead to the better understanding of soil health, especially in oil palm plantation. Further studies should be carried out to study sustainability of soil green algae as soil quality indicator.